Consensus CPHD filter for distributed multitarget tracking - Battistelli, G.; Chisci, L.; Fantacci, Claudio; Farina, A.; Graziano, A. (Institute of Electrical and Electronic Engineers, 2013)
The paper addresses distributed multitarget tracking over a network of heterogeneous and geographically dispersed nodes with sensing, communication and processing capabilities. The contribution has been to develop a novel consensus Gaussian Mixture-Cardinalized Probability Hypothesis Density (GM-CPHD) filter that provides a fully distributed, scalable and computationally efficient solution to the problem. The effectiveness of the proposed approach is demonstrated via simulation experiments on realistic scenarios.